1988
DOI: 10.1111/j.1471-4159.1988.tb04871.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of Two mRNAs Encoding Active Rat Tryptophan Hydroxylase

Abstract: Two full-length cDNA clones that encode functional rat tryptophan hydroxylase (EC 1.14.16.4), the key enzyme in serotonin synthesis, have been isolated from a rat pineal gland library. These two clones correspond to the 1.8- and 4-kilobase mRNA species, respectively. They contain the same coding sequence corresponding to a 51,010-dalton protein and differ in the length of their 3' untranslated regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 26 publications
4
93
0
2
Order By: Relevance
“…2 RT-PCR analysis of TPH transcripts in the retina of adult Brown Norway rats. The size of the amplified products is 254 bp (lane1) and, as demonstrated by sequencing, corresponds exactly to a fragment of mRNAs for TPH cloned by Darmon et al (1988). Lane 2, negative control, H20; M, marker standard.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…2 RT-PCR analysis of TPH transcripts in the retina of adult Brown Norway rats. The size of the amplified products is 254 bp (lane1) and, as demonstrated by sequencing, corresponds exactly to a fragment of mRNAs for TPH cloned by Darmon et al (1988). Lane 2, negative control, H20; M, marker standard.…”
Section: Discussionmentioning
confidence: 85%
“…described (Table 2) (Darmon et al 1988). Their specificity was analysed by comparing their sequences to various gene sequence databases, using the European Molecular Biology Laboratory (EMBL) Network File Server and the Fasta Program (Pearson and Lipman 1988).…”
Section: Rt-pcrmentioning
confidence: 99%
“…The TPH gene has been cloned from a variety of species including rodents, rabbits, and humans (Darmon et al, 1986(Darmon et al, , 1988Grenett et al, 1987;Boularand et al, 1990;Stoll et al, 1990;Kim et al, 1991;Tipper et al, 1994). In general, the rodent studies showed that cDNA probes hybridized to two mRNA species from RNA isolated from rat pineal or mouse mastocytoma cells (Dannon et al, 1988;Stoll et al, 1990;Kim& al., 1991).…”
mentioning
confidence: 99%
“…Physicochemical, enzymic and immunochemical properties differed between TPHs of neural and non-neural tissue origin, and it is accepted that neural TPH might be a different entity from the non-neural enzyme [8,10,12,13]. Complimentary DNAs of TPH have been cloned from various sources but no differences or only trivial variation in amino acid sequences were found among them [14][15][16][17][18][19]. The molecular basis of differences between the neural and non-neural enzymes has not yet been explained.…”
mentioning
confidence: 99%